Pharmaceutical Micropollutants Removal and n2o Production by Nitrification Process in Sbr and Sbbr: A Review - Pages-Diaz, J; Hernandez-Velez, L (Springer Science and Business Media B.V., 2025)
Pharmaceutical micropollutants (PMPs) can cause significant environmental risks, with trace levels of exposure harming humans and wildlife. Biotransformation is a high-potential and low-cost way to remove PMPs, where ammonia-oxidizing microorganisms (AOM) are essential for eliminating pharmaceutical micropollutants. On the other hand, AOM are associated with nitrous oxide (N2O) emission generation in nitrifying. In this sense, micropollutants can inhibit the activity of AOB, reducing the ammonia oxidation rate and increasing N2O emissions. To mitigate these challenges, systems that allow satisfactory performance of the metabolism of AOB and NOB, such as the Sequencing Batch Reactor (SBR) and Sequencing Batch Biofilm Reactor (SBBR), are essential. However, no systematic review of the advances or gaps in this field has been published, mainly focused on SBR or SBBR. Thus, this work reviews recent advances regarding PMP biotransformation and N2O production by AOM, emphasizing SBR and SBBR systems. Besides, we compare the removal performances of various micropollutants in biological processes. The biotransformation of emerging pollutants was also presented to explore the metabolic pathways of N2O production and the critical factors that influence N2O emissions in biological processes. Controlling DO levels, intermittent aeration, and maintaining low ammonium concentrations can help mitigate N2O emissions. The simultaneous removal of PMPs and N2O emissions was also analyzed; however, there is still limited research regarding the effect of PMPs on N2O emission production in the nitrification process using SBR or SBBR. However, SBBRs may provide a more stable platform for both PMP removal and minimized emissions, mainly when biofilm characteristics and intermittent aeration are well managed. Thus, this review gives a complete vision of the advances of SBR and SBBR to remove PMPs and minimize the N2O, as well as the future directions that research needs to address to improve the PMPs biotransformation and N2O minimization. © The Author(s), under exclusive licence to Springer Nature B.V. 2025.
Keywords: Biofilm; Nitrous oxide; Pharmaceutical micropollutants; Sequencing batch reactor